Strategi Coping Stres pada Studi Mahasiswa yang Bekerja di JABODETABEK - Lintang Dwi Aprilia; Nasichah; Shabilla Noor Rachma; M. Ubaidillah; Shafina Tunnazah (Jurnal Pendidikan Sosial Dan Konseling, 2023)
This research describes several stress coping strategies for working students. The main focus of students is studying. Not infrequently, besides studying, students also work. In this case, students must divide their time between study and work. This research aims to explain stress coping strategies for working students. This research uses quantitative methods, using a questionnaire (google form) as a data collection technique. The objects of this research are Jabodetabek students who are pursuing undergraduate (S1) education while working. From the data that has been obtained, it can be explained that effective stress coping strategies for working students include: accepting that stress is part of life, accepting the fact that not everything can go as desired, trying to see problems from a different perspective, involving yourself in religious matters, telling stories to friends and family, doing things you like, looking for solutions, understanding the causes of the stress you are experiencing, not being afraid to take risks, withdrawing from other people when facing problems, and sometimes avoiding situations that can remind you on the problems being faced is also an effective coping strategy for them (respondents).